Phenolic Compounds Chemistry, Synthesis, Diversity, Non-Conventional Industrial, Pharmaceutical and Therapeutic Applications - Badria, Farid A. (Biochemistry, 2022)
Phenolics are commonly available compounds in foods, beverages, and spices. They have great importance in all aspects of daily life including industry, health, and research. As such, this book presents a comprehensive overview of phenolic compounds and their potential applications in industry, environment, and public health. Chapters cover such topics as the production of these compounds and their uses in environmental sustainability, climate change, green industry, and treatment of human disease.